RNA expression and risk of venous thromboembolism in lung cancer - Tamara A. Sussman (Wiley, 2020)
Abstract Background The propensity to develop venous thromboembolism (VTE) on the basis of individual tumor biological features remains unknown. Objectives We conducted a whole transcriptome RNA sequencing strategy, focusing on a single cancer type (lung cancer), to identify biomarkers of cancer‐associated VTE. Methods Twelve propensity‐matched patients, 6 each with or without VTE, were identified from a prospective institutional review board–approved registry at the Cleveland Clinic with available tissue from surgical excision of a primary lung mass between 2010 and 2015. Patients were propensity matched based on age, sex, race, history of prior cancer, date of cancer diagnosis, stage, histology, number of lines of chemotherapy, and length of follow‐up. RNA sequencing was performed on tumor tissue, and gene set enrichment analysis (GSEA) was performed on differentially expressed genes. Results We identified 1037 genes with differential expression. In patients with VTE, 869 genes were overexpressed and 168 were underexpressed compared to patients without VTE. Of these, 276 overexpressed and 35 underexpressed were significantly different (Q < 0.05). GSEA revealed upregulation of genes in complement, inflammation, and KRAS signaling pathways in tumors from patients with VTE. Conclusions These differentially expressed genes and associated pathways provide biologic insights into cancer‐associated VTE and may provide insignts to develop new risk stratification schemes, prevention, or treatment strategies.